Bank Aceh Syariah Contribution in Supporting the Development of the Halal Tourism Sector In the City of Sabang - Dara Amanatillah Amanatillah; Isnaliana Isnaliana; Jalilah Jalilah (University of Darussalam Gontor, 2023)
The presence of halal tourism does not only focus on halal products, which are life choices and follow Sharia rules for the community, but the involvement of the government and Islamic financial institutions, especially Islamic banking, is also a supporter of encouraging this sector, one of which is Bank Aceh Syariah. This research focused on contribution of Bank Aceh Syariah in supporting the development of the Halal tourism sector especially the MSME actors in the city of Sabang. This methodology used in this research is descriptive qualitative based on field research. The findings of the research stated that the contribution of Bank Aceh Syariah to supporting the development of the halal tourism sector in the city of Sabang is particularly carried out through fund distribution products, namely microfinance with murabahah and musyarakah schemes for MSME actors. However, Bank Aceh Syariah focuses not only on the financial aspect alone but also on assistance and supervision for MSME actors. In addition, the convenience of service facilities provided by Bank Aceh is also a supporting facility in facilitating transactions for business people and visiting tourists, such as the convenience of ATM facilities, Mobile ACTION, QRIS, and other facilities.